Protest as Argument - Bowell, Tracy (Informal Logic)

(untitled) (Informal Logic, 2026)
The right to protest is often considered a key element of democracy, and protest has a long history in both democracies and authoritarian states. Protest communicates opposition, support, or solidarity. Aimed at changing people’s minds, it can influence beliefs about an issue, raise awareness of and inform about an injustice or a crisis, and influence emotional responses. I consider the extent to which protest can plausibly be considered argument and a legitimate part of public discourse. Starting with John Delicath’s and Kevin Deluca’s ideas about ‘image events’ and argumentative practice (2023), I consider protests as examples of multi-modal arguments. Then, drawing on Moria Howes’ and Catherine Hundleby’s work on the role of emotion in argument, I reflect on the way in which multi-modal analyses provide resources for understanding the role of emotion in argument and consider the ways in which emotions contribute to argument in the context of protest.